2018
DOI: 10.16965/ijpr.2017.262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abdominal Exercise on Respiratory Muscles and Pulmonary Function in Healthy Males

Abstract: Background: Abdominal muscle is the major expiratory muscle and play an important role in ventilation. The purpose of this study is to examine the effects of abdominal muscle training on pulmonary function. Subjects were randomly assigned to low (n=7), moderate (n=7), and high intensity (n=7) groups and performed sit-up exercises at for 6 weeks. The intensity was set at 40% (low), and 80% (high) of the numbers of sit-ups they performed during 1-min sit-up test. Baseline and post-training measurements included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Abdominal exercises, according to prior research, not only improve abdominal muscle strength but also alter the diaphragm and inspiratory muscle function. According to Shao et al [38], abdominal muscle exercise, as a major muscle of expiration, resulted in an increase in MEP and a significant increase in maximal voluntary ventilation in healthy individuals, which is similar to our findings. in addition, after abdominal exercise, dePalo et al [39] found a significant increase in transdiaphragmatic pressure, maximum inspiratory and expiratory pressures in healthy adults.…”
Section: Discussionsupporting
confidence: 93%
“…Abdominal exercises, according to prior research, not only improve abdominal muscle strength but also alter the diaphragm and inspiratory muscle function. According to Shao et al [38], abdominal muscle exercise, as a major muscle of expiration, resulted in an increase in MEP and a significant increase in maximal voluntary ventilation in healthy individuals, which is similar to our findings. in addition, after abdominal exercise, dePalo et al [39] found a significant increase in transdiaphragmatic pressure, maximum inspiratory and expiratory pressures in healthy adults.…”
Section: Discussionsupporting
confidence: 93%
“…And During forced expiration, ribcage deformation consisted of a rounding of the lower rib cage with the transverse dimension decreasing more rapidly than the lower anteroposterior dimension. [12] The results of the present study is also consistent with a study by Shweta Modi, Sweety Shah where they included 15 middle aged women and found that 15 days of abdominal muscle strengthening exercise (curls up ) enhanced Peak Expiratory Flow Rate. Here, Increase in peak expiratory flow rate is due to pressure on diaphragms that exert by number of abdominal wall muscles.…”
Section: Discussionsupporting
confidence: 92%
“…In turn, there is raised pleural pressure and alveolar pressure which drives air out of the lungs. [12] Diaphragm strengthening achieved by abdominal exercises helps in maintaining an optimum length tension relationship of diaphragm, thereby increasing lung and chest wall compliance. [18] The ADAPTIVE changes in the muscles determined by the exercise can account for the results of the study, since the metabolic capabilities of the muscles were continuously overloaded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation